2016
DOI: 10.1097/gox.0000000000001070
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Malignant Transformation of Oral Lichen Planus of the Mandible

Abstract: Summary:Oral lichen planus (OLP) is an immune-mediated mucocutaneous disease associated with an increased risk in oral squamous cell carcinoma (OSCC). Nearly all cases of malignant transformation have been reported in patients >40 years old. We report the case of a 37-year-old woman with a 5-year history of erosive OLP who presented with malignant transformation to OSCC. Delineating the margins of the disease was impossible at presentation given her OLP, and she was initially treated with concurrent chemoradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…8 Based on a review of the literature, there is evidence to support the malignant potential of oral LP. 9 One particular review found that those with erosive or atrophic oral LP are more likely to undergo malignant transformation than any other subtype of LP. 10 While another found that those with LP lesions on the tongue had 1.82 times the risk of developing oral SCC.…”
Section: Discussionmentioning
confidence: 99%
“…8 Based on a review of the literature, there is evidence to support the malignant potential of oral LP. 9 One particular review found that those with erosive or atrophic oral LP are more likely to undergo malignant transformation than any other subtype of LP. 10 While another found that those with LP lesions on the tongue had 1.82 times the risk of developing oral SCC.…”
Section: Discussionmentioning
confidence: 99%
“…The questions that remained unanswered are to which degree OLP is independent from the OSCCs and whether the carcinoma has developed from the OLP or is it just a coincidence. [27] The malignant transformation was described for the first time in the distant 1965. [28] The epidemiological data suggests that the malignant transformation of OLP is not equally represented in all the regions of the oral cavity.…”
Section: Etiopathogenic Problems With Olpmentioning
confidence: 99%
“…[30] The most common malignant transformation of OLP is OSCCs, with extremely uncertain prognosis and life threatening condition. [27] The pathogenesis of OLP is very complex and includes a possible antigen presentation from the oral keratinocytes the origin of which can be exogenous or endogenous. [31][32][33] This antigen activator is accompanied by a mixed inflammatory response that is consisted mainly of T-cells, macrophage, mast cells as well as cytotoxins and cytotoxic molecules.…”
Section: Etiopathogenic Problems With Olpmentioning
confidence: 99%